EXPANDED ENDONASAL TRANSSPHENOIDAL SURGERY FOR THE RESECTION OF TUBERCULUM SELLAE MENINGIOMA: DESCRIPTION OF SURGICAL TECHNIQUE AND REVIEW OF LITERATURE - Khasanov , Khabibullo; Alikhodjayeva , Gulnara; Yakubov , Jakhongir; Babakhanov , Bakhodir; Jurakulov , Elnur; Takeuchi , Kazuhito (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Meningiomas with originating from tuberculum sellae, sphenoid platform, and optic chiasmatic groove are collectively called as tuberculum sellae meningiomas (TSMs) and they are accounted for 5 to 10% of all intracranial meningiomas, which invade the optic canals and lead to visual impairment by displacing the optic nerves upward and laterally. Except presence of many transcranial microsurgical approaches, introduction of endoscopes with highest magnification and gaining much experience in this have made the endonasal route feasible for the resection of tuberculum sellae meningiomas. There are various case reports and mixed publication series discussing this approach. Despite pituitary adenomas, craniopharyngiomas, the literatures describing the surgical steps of endoscopic endonasal transsphenoidal surgery for the resection of tuberculum sellae meningiomas in detail are lacking The objective of our research is to review recent literatures about endoscopic endonasal transsphenoidal surgery for the removal of tuberculum sellae meningiomas and describe surgical procedures step by step in a easy way for young neurosurgeons of developing countries. Methods: In this study, we are going to review recent publications about endoscopic endonasal transsphenoidal surgery for the resection of TSMs by using Pubmed and Embase for the past ten years but, In this study, some older publications with significant importance were also included. The following key word for search in various combinations were used: tuberculum sellae, meningioma, endoscopy, tuberculum sellae meningioma, transsphenoidal surgery, transcranial surgery. Results: A total of 27 publications including mixed case reports, original studies, systematic analyzes and review articles, video presentations were reviewed from the Pubmed and Embase database for the past ten years. Relevant anatomical knowledge and surgical procedure descriptions are collected. With the help of obtained information endoscopic endonasal transsphenoidal surgery explained step by step. Conclusion: Except from traditional transcranial microsurgical approaches, recently introduced and being developed endoscopic techniques for the resection of tuberculum sellae meningiomas can be helpful by minimizing wide craniotomy approach related complications. Improvement in various skull base reconstruction methods decrease postoperative complications.